PELAKSANAAN SISTEM PERADILAN ANAK DI INDONESIATERHADAP ANAK BERHADAPAN DENGAN HUKUM - heri sudaryanto (Jurnal Idea Hukum, 2022)
The juvenile criminal justice system is the entire process of resolving child cases that face the law from the investigation stage to the guidance stage after undergoing criminal proceedings based on protection, justice, non-discrimination, best interests for the child, respect for children, survival and child development, proportional, deprivation of independence and prosecution as a last resort and avoidance of retaliation. The type of research conducted is descriptive research with normative legal research types related to the implementation of the juvenile justice system that is faced with the law. The results showed that the implementation of the juvenile justice system against children who faced the law had been implemented in accordance with the legislation No. 11 of 2012 concerning the juvenile justice system. The implentation of the implementation of children who face the law in the juvenile justice process is done through a diversion approach. Government efforts in protecting children who face the law are carried out with investigation efforts, prosecutions up to the trial process. These protection efforts are pursued by the diversion process. If the implementation of this diversion cannot be done eating the judicial process is to become ultimum remidium while still paying attention to the best interests of the child by placing children in LPAS, LPAK and LPKS which the institution is expected to be able to provide new expectations and protection for children who face the law.